THE ROLE OF INSTITUTIONS AND GLOBALIZATION TOWARDS INCLUSIVE AND SUSTAINABLE GREEN DEVELOPMENT (INCLUSIVE GREEN GROWTH) - Arka, Sudarsana; Purwanti, Ni Putu Pramitha; Wenagama, I Wayan; Putra Yasa, I Made; Aryasthini Mahaendrayasa, I Made Sinthya (Jurnal Ekonomi Kuantitatif Terapan; Vol 17 No 1 (2024): Vol. 17, No. 1, Februari 2024 (pp.1-154)DO - 10.24843/JEKT.2024.v17.i01.p10, 2024)
The idea of ?? a green economy does not replace sustainable development, but creates a new focus on the economy, investment, capital and infrastructure, jobs and skills as well as positive social and environmental outcomes. The green economy is closely related to SDGs No. 13, climate action, but, even further, this concept directs attention to the quality of life with people at the center. This research tries to see the impact of the development of inclusive green growth in several countries on the welfare of their people. Inclusive green growth prioritizes planetary and human health, and considers them interrelated. Prioritization and implementation of green initiatives also helps countries achieve various sustainable development goals. The hypothesis tested is that countries that implement inclusive green growth in their development policies will have a strong correlation with community welfare, governance of government institutions, and economic openness in the context of international trade. The results of data analysis show that inclusive green growth has a positive and insignificant effect on economic openness in various countries. Government institutional governance has a positive and insignificant effect on economic openness in various countries. Inclusive green growth has a positive and significant effect on the welfare of society in various countries. The governance of government institutions has a negative and insignificant effect on the welfare of society in various countries. Economic openness has a positive and significant effect on the welfare of society in various countries. Inclusive green growth does not have an indirect effect on the welfare of society in various countries. The governance of government institutions does not indirectly influence the welfare of society in various countries.